The Influence of Profitability and Company Growth on Earnings Management in The Consumer Goods Industry Sector - Jumliana; Yusdiman; Dg Macenning, A. Reski Almaida (Journal of Economics and Management Technologies, 2025)
Objectives - This study aims to identify the influence of Return on Assets (ROA), Return on Equity (ROE), and Company Growth on Earnings Management in the Consumer Goods Industry sector, specifically in the Cosmetics and Household Needs sub-sector listed on the Indonesia Stock Exchange. Methods - The analysis methods employed include descriptive analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing (both partial and simultaneous), and the coefficient of determination test (R²). The results - Return on Assets (ROA) has a direct positive and significant effect on Earnings Management, with a significance level of 0.021. Return on Equity (ROE) also has a direct positive and significant effect on Earnings Management, with a significance level of 0.001. Company Growth likewise has a positive and significant effect on Earnings Management, with a significance level of 0.046, which is less than 0.05. Furthermore, ROA, ROE, and Company Growth simultaneously have a positive and significant effect on Earnings Management, with a significance level of 0.001.